The Importance of Drug Safety and the Strategies for Promoting it - Papoyan, Tatshat («Տնտեսագետ» հրատ․)
With medications becoming the standard of treatment for many illnesses these days, drug safety has turned into a high priority in contemporary healthcare. Medicines might offer therapeutic benefits but carry side effects and risks. Drug safety is crucial for positive patient outcome, injury prevention, and lower healthcare expenditures. This particular paper offers a sweeping review of the significance of drug safety and also covers drug development, regulation, surveillance and control of unwanted side effects. The literature review points to the difficulty of drug safety because of patient variables including age, health condition and concurrent medicine. Specific care is required for vulnerable groups - people that are older, kids or even pregnant - who present considerable safety risks. Preclinical testing is informative but clinical trials with human subjects are still crucial for evaluating efficacy and drug safety before marketing. The paper discusses the crucial role of drug safety in public health and also offers views on its intricacy and advancement methods.
Keywords: Markets and Competition